Model Pembelajaran Gerak Dasar Lompat Dengan Permainan Sumbar - Prakoso, Ricky (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2015)
The purpose of this study is to produce a model of learning basic movement jump through games sumbar(stacking images) that can help teachers and students in learning penjasorkes. This study uses a method whichis the basis for the development as for the procedures/steps are as follows: (1) to analyze the product to bedeveloped; (2) developing initial products; (3) expert validation and revision; (4) small group testing andrevision of the product; (5) field testing and final product; (6) revision of the final product; and (7) the outcomeboast a game modification (stacking images) were generated through field trials revision. From the test resultsobtained penjas learning expert evaluation data, from both experts, stated that the development of modelsalready boasts a game in the category of good judgment. However, there needs to be repaired, because there are few alternative answers are still pretty good claim. The trial of small group 92.8% (very good), and field trials 93.6% (very good). From these results, it can be concluded models game sumbar (stacking images) for learning basic movement jump fit for use.